Управління персоналом і самоменеджмент у системі управління організацією в умовах сучасних викликів - Василик, С. К.; Прохоровська, С. А.; Агєєва, Ірина Вікторівна; Ahieieva, Iryna (My University, 2023)
UA: В статті розглянуто актуальну на сьогодні взаємодію між управлінням персоналом і самоменеджментом як елементів взаємодії у менеджменті. Метою статті являється аналіз проблем і перспектив управління персоналом у системі управління організацією в умовах сучасних викликів. Досліджено специфіку управління персоналом, її завдання й функції. Розглянуто функції, завдання, сильні сторони та недоліки самоменеджменту. Практична цінність роботи полягає в результатах дослідження й подальших пошуках спеціалістів економічного сектору. /// EN: The article is devoted to the peculiarities of personnel management and the influence of martial law on this process. Theoretical and method ological approaches to the formation of concepts of personnel management and tasks, as well as the basic principles of their implementation are considered. The personnel management at the modern stage undergoes constant changes. The concepts of "self-management" and "personnel management" are related to the success of the company, which means the state. An important factor is the improvement of the efficiency of the use of human resources in the field of trade, and their constant improvement of the concept of personnel management. This article is an analysis of the problems and prospects of personnel management in the organization management system in the conditions of modern challenges. The research results are presented based on relevance. The author argues that self-management is a complex innovative science that is only emerging alongside with the formation of a market economy. The self-management as a component of professional development allows for continuous improvement. Researching of personnel readiness for self-development and application technologies of self-management are carried out. Modern personnel-technologies for increasing the efficiency of personnel management within the organization are proposed, based on the experience of foreign countries. The scheme of selfmanagement based on competences has been formulated. At the modern stage, personnel management has seen changes, but thanks to technologies and innovations, the development of management contributes to the development of the economy. The practical value of the work lies in the results of the study, which can be applied to further searches of the economic sector.
Keywords: менеджмент; схема управління персоналом; самоменеджмент; сучасні виклики; внутрішні ресурси підприємства; якості менеджера; management; personal management scheme; self-management; modern challenges; internal resources of the enterprise; qualities of a manager